The prediction of wrinkle formation in non-crimp fabrics during double diaphragm forming - Yu, Fei (2022)
Liquid composite moulding (LCM) processes are an economical alternative to autoclave-cured prepreg, as intermediate material forms are less expensive, capital equipment costs are lower and cycle times are shorter. LCM is suitable for producing aerospace quality components, but the process chain is dependent on a separate preforming process to convert 2D fibre formats into complex 3D shapes prior to moulding. Preforming is difficult to automate to ensure defect-free architectures, as multiple plies are often formed at the same time according to predefined forming loads and constraints. Corrections to the draping direction, force and sequence can be easily refined during manual hand layup, as the laminator works on one ply at a time. Corrections to the forming sequence cannot be easily made during automated forming, therefore numerical models are required during the design phase to refine process parameters to ensure that defects do not evolve. This thesis seeks to develop a robust simulation methodology for modelling the forming behaviour of biaxial fabrics, in order to enable effective identification of forming related defects and assist in process design for improving the quality of preforms. Research has been conducted in three main areas: